2015
DOI: 10.1007/s10147-015-0860-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term low-volume hydration in cisplatin-based chemotherapy for patients with lung cancer: the second prospective feasibility study in the Okayama Lung Cancer Study Group Trial 1201

Abstract: This prospective study demonstrated the safety and efficacy of shorter-term lower-volume hydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
2
17
1
Order By: Relevance
“…Ninomiya et al conducted a prospective, low‐volume hydration feasibility trial (950 mL total during outpatient infusion and 3.5 L oral posthydration) in chemo‐naïve lung cancer patients ( n = 45) receiving cisplatin ≥60 mg/m 2 . During the first cycle, only one patient experienced grade ≥2 nephrotoxicity (2%), and five patients (11%) experienced a grade ≥1 event . Bohm et al also showed that low‐volume hydration (2.25 L total) provided nephroprotection in ovarian cancer patients ( n = 26) receiving cisplatin 90 mg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninomiya et al conducted a prospective, low‐volume hydration feasibility trial (950 mL total during outpatient infusion and 3.5 L oral posthydration) in chemo‐naïve lung cancer patients ( n = 45) receiving cisplatin ≥60 mg/m 2 . During the first cycle, only one patient experienced grade ≥2 nephrotoxicity (2%), and five patients (11%) experienced a grade ≥1 event . Bohm et al also showed that low‐volume hydration (2.25 L total) provided nephroprotection in ovarian cancer patients ( n = 26) receiving cisplatin 90 mg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Early studies established the importance of CH during cisplatin administration in the inpatient setting. However, safe and effective cisplatin administration with short‐duration and/or low‐volume hydration is feasible in the outpatient setting .…”
Section: Discussionmentioning
confidence: 99%
“…The aprepitant regimen not only had a positive impact on health outcomes and QOL for patients receiving cisplatin-based chemotherapy, but also counterbalanced incremental total medical costs including indirect costs that would be wasted by CINV without it. 29 However, the ICER slightly exceeded the WTP threshold in the ICS (6 195 [30][31][32] Furthermore, aprepitant was used in an antiemetic regimen to prevent CINV in those studies. NK 1 RA and other newer generation antiemetics have markedly improved gastrointestinal toxicity induced by cisplatin, [12][13][14][15][33][34][35] which may enable oral hydration.…”
Section: Discussionmentioning
confidence: 98%
“…Univariate sensitivity analysis indicated that factors that mainly affected these results included cost of aprepitant and CR rate. Recently, short hydration was shown to improve QOL for patients who received cisplatin‐based chemotherapy . Furthermore, aprepitant was used in an antiemetic regimen to prevent CINV in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Single arm retrospective studies performed by Brock and Alberts (30), Tiseo et al (19) and Lavole et al (21) with patient numbers of 147, 107 and 357 showed the feasibility of short hydration for cisplatin administration. Four single arm prospective studies, one involving 44 patients and performed by Horinouchi et al (22), one involving 46 patients and performed by Hotta et al (23), one involving 45 patients and performed by Ninomiya et al (24) and one involving 46 patients and performed by Horinouchi et al (26) also demonstrated the safety of short hydration for cisplatin. In addition, Ouchi et al (27) retrospectively compared a short hydration protocol performed in 13 patients with a conventional hydration protocol performed in 17 patients and showed a similar safety between the two groups.…”
Section: Discussionmentioning
confidence: 99%